Pengaruh Pemahaman Investasi, Dengan Modal Minimal Dan Motivasi Terhadap Minat Mahasiswa Dalam Melakukan Investasi Di Pasar Modal Syariah - M Samsul Haidir (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2019)
Effect of Investment Understanding, Minimum Investment Capital and Motivation on Student Interest in Investing in Islamic Capital Markets. This study aims to determine how the influence of understanding of investment, minimum capital, and motivation towards the interest of students investing in the Islamic capital market. The study used a descriptive quantitative method. Respondents in this study were students of Sunan Kalijaga UIN from semester 2 to 6 through questionnaires. The results of this study indicate that the understanding of investments held by a good student who has studied Islamic investment management or not, does not affect the interest of students to invest in the Islamic capital market. However, with a small minimum capital and motivation from oneself and others, it greatly influences students to invest in the Islamic capital market. However, with the minimum capital ketch and motivation of themselves and others greatly affect the student to invest in the Islamic capital market. The purpose of this study is to find out whether investment knowledge, minimum capital and investment motivation affect student interest in investing in the Islamic capital market. Therefore, public education is needed from saving society to investing society to increase interest in investing.